2008
DOI: 10.1080/87565640802254471
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive Test Profiles of Extremely Low Birth Weight Five-Year-Old Children Differ According to Neuromotor Status

Abstract: The neurocognitive outcome of children born with extremely low birth weight (ELBW) is highly variable due to the complexity of morbidity. So far, no study has compared comprehensive neuropsychological test profiles in groups with different neuromotor status. In a national cohort of ELBW children neuropsychological test profiles were assessed in 4 groups defined according to a neurological examination at 5 years of age: normal neuromotor status (N = 56), motor coordination problems (N = 32), multiple subtle neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 48 publications
1
20
0
2
Order By: Relevance
“…There is a strong association between MND and cognitive development and neuropsychological problems. Preterm or term children diagnosed with MND have been found to have lower IQ compared with children with normal neurological examination findings . In addition, children diagnosed with MND have a higher prevalence of psychiatric problems .…”
Section: Discussionmentioning
confidence: 99%
“…There is a strong association between MND and cognitive development and neuropsychological problems. Preterm or term children diagnosed with MND have been found to have lower IQ compared with children with normal neurological examination findings . In addition, children diagnosed with MND have a higher prevalence of psychiatric problems .…”
Section: Discussionmentioning
confidence: 99%
“…Los niños con BPN tienen dificultades en el control motor fino y grueso, que se evidencia desde los primeros días de nacidos y que suele mantenerse a lo largo de su desarrollo, a diferencia de los niños con PNN quienes presentan mejores respuestas motrices y para los que un desarrollo de esta esfera será más favorable (Aliabadi y Kachosangi, 2012;Anderson y Dewey, 2011;Barón et al, 2011;Bermúdez et al, 2012;Cifuentes et al, 2012;Dewey et al, 1999;Gidley et al, 2010;Korkman et al, 2008;Sue et al, 2012).…”
Section: Discussionunclassified
“…A nivel conductual, se ha correlacionado con hiperactividad y problemas emocionales. Los niños que presentan BPN suelen presentar bajos perfiles en pruebas neuropsicológicas y cognitivas Anderson y Dewey, 2011;Barón, Erickson, Ahronovich, Baker y Litman, 2011;Bermúdez et al, 2012;Dewey et al, 1999;Gidley et al, 2010;Korkman et al, 2008;Sue et al, 2012).…”
Section: Introductionunclassified
“…This study focused on a national Finnish ELBW cohort, which consisted of 351 infants born alive in 1996-1997 (24). Follow-up results have been published until preschool age (2,5,17,20,24). Of the 206 children alive at five years of age (17), 17 were severely disabled and therefore excluded from this study.…”
Section: Study Groupmentioning
confidence: 99%
“…Most infants born before 28 weeks of gestation and with an extremely low birth weight (ELBW) of less than 1000 g survive, but they face an increased risk of neurosensory morbidities, including cerebral palsy, intellectual disability, visual impairments and auditory deficits (1)(2)(3)(4). Long-term follow-up studies have revealed a high risk of cognitive dysfunction with both general and specific difficulties in cognitive, academic and behavioural functioning, as evidenced by both neuropsychological assessments and parental evaluations (5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%